Stryphnodendron species known as barbatimão: A comprehensive report - Souza-Moreira, Tatiana M. [UNESP]; Queiroz-Fernandes, Geisiany M.; Pietro, Rosemeire C.L.R. [UNESP] (MDPI, 2018)
Stryphnodendron spp., popularly known as barbatimão, is the native Brazilian tree most often employed to treat wounds and infections. The aim of the present study was to highlight the importance of S. adstringens, as well as other Stryphnodendron species recognized as barbatimão, to human health, depicting the relevance of ethnopharmacological knowledge to scientific evidence for uses, related chemical compounds, development of pharmaceutical formulations, and the establishment of toxicity parameters. For this purpose, the literature databases PubMed, Scielo, Lilacs, CAPES Thesis and Google Scholar were searched until 2017. It was observed that stem bark was the primary part of the plant used, mainly as a decoction, for wound healing and treatment of infectious and inflammatory disorders. Confirmed biological activities, including wound healing, anti-inflammatory antioxidant, and antimicrobial activities, were related to the presence of compounds from tannin class, mostly proanthocyanidins. Toxicity parameters for stem bark were inconclusive, but toxicity was observed to a significant extent when seeds were ingested by cattle or other animals. Due to these important and confirmed biological activities, government policy encourages the phytotherapic use of S. adstringens, and some formulations with stem bark extracts were developed and patented. Furthermore, antiprotozoal, hypoglycemic and antiviral activities were identified as promising.
Keywords: Biological activity; Catechin; Ethnopharmacology; Medicinal plant; Tannin; Wound healing